JUNIOR STUDENTS’ INTEREST IN SCIENCE COURSES BASED ON HOTS LITERACY PROGRAM: MODELING OF SCIENTIFIC INTEREST AND ITS RELATIONSHIPS WITH OTHER COMPONENTS - Bunawan, Wawan; Gultom, Syamsul; Rismawati; Kristina, Efa; Ash Suci, Fidya Witria; Josephine, Anggi Anggana (International Journal of Research -GRANTHAALAYAH, 2021)
This study aims to describe the pattern of relationships between several factors supporting interest (interest) in science subjects. Students get an Exercise Program to improve scientific literacy. This training program aims to improve students' scientific literacy skills. The training program is carried out after the teachers receive the training program. The study of students' interest in science was revealed by conducting a survey related to several factors supporting interest in science. Several factors in the study of supporting scientific interests include the role of teachers, parental support, school roles, peer support, physics, chemistry and biology materials. Research participants were taken using random sampling technique, totaling 39 students. The developed scientific literacy assistance program seeks to improve the quality of learning outcomes. The success of the scientific literacy training program is related to students' scientific interest. The results showed that the multiple linear regression model provides a descriptive numerical description of the empirical relationship between the value of interest in science and its supporting components. Likewise, interest has a role in learning achievement.